Experimental Evaluation on the Influence of RCD Snubbers in a 3-Level Thyristor Based MLCR CSC - Bhaba P. Das; Neville R. Watson; Yonghe Liu (Journal of Engineering)
Multilevel current reinjection (MLCR) concept provides self-commutation capability to thyristors, enabling thyristor based current source converters (CSC) to operate under negative firing angle. It also lowers the input current harmonic distortion. This is achieved by using an auxiliary reinjection bridge. Extensive experimental results are presented in this paper to analyse the performance of the 3-level MLCR CSC for different snubber components across the reinjection bridge. The trade-off in the choice of the snubber circuit is illustrated, with its influence on the AC side line current and DC side output voltage of the 3-level MLCR CSC.